Bile Acid Detection Techniques and Bile Acid-Related Diseases - Zhao, Xiang; Liu, Zitian; Sun, Fuyun; Yao, Lunjin; Yang, Guangwei; Wang, Kexin (Frontiers in Physiology, 2022)
Bile acid is a derivative of cholinergic acid (steroidal parent nucleus) that plays an important role in digestion, absorption, and metabolism. In recent years, bile acids have been identified as signaling molecules that regulate self-metabolism, lipid metabolism, energy balance, and glucose metabolism. The detection of fine changes in bile acids caused by metabolism, disease, or individual differences has become a research hotspot. At present, there are many related techniques, such as enzyme analysis, immunoassays, and chromatography, that are used for bile acid detection. These methods have been applied in clinical practice and laboratory research to varying degrees. However, mainstream detection technology is constantly updated and replaced with the passage of time, proffering new detection technologies. Previously, gas chromatography (GS) and gas chromatography-mass spectrometry (GC-MS) were the most commonly used for bile acid detection. In recent years, high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) has developed rapidly and has gradually become the mainstream bile acid sample separation and detection technology. In this review, the basic principles, development and progress of technology, applicability, advantages, and disadvantages of various detection techniques are discussed and the changes in bile acids caused by related diseases are summarized.